A study of the vocational preferences of the public and private high school seniors in the City of Manila - Campos, Dolores (Lopez) 1905- (College of Education, University of the Philippines Diliman, 1949)
An attempt to study the vocational preferences of senior students in the public and private high schools in the City of Manila for the school year 1948-49, this investigation revealed several matters that have implications for vocational guidance. The study included 2862 seniors from 3 public and 11 private high schools. A great number of these students are planning to go directly to college while a little less than one-tenth are contemplating to go to vocational schools. They were very much influenced in their vocational choices by their parents, their favorite school subjects and by their own natural preferences. Like any ambitious though reasonably conceived plan, the proposed vocational guidance program can be started here and now by utilizing what guidance facilities are available and improving them along certain lines.